An Introduction to 5-step Brand Management Conditions for the Nyírerdő Zrt. "GÚTH HUNTING AREA" - Magyar Zoltán; Мадьяр Золтан (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract "Hunting" has now become a prominent tourism motive and the role of "hunting tourism" in shaping the image of the country and destination has become clear. Hunting tourism can be considered as a form of niche tourism, a form of tourism in an authentic environment, motivated by special interests and therefore only reaching a limited group of consumers. The number of foreign guest hunters visiting Hungary is steadily increasing, reaching 29,000 in 2022. Foreign hunters visiting our country are involved in the service process developed by the hunters, with the assistance of the service providers. Their satisfaction or dissatisfaction with a particular service provider is based on their experience of each service element, but their experience also fundamentally influences and shapes the image of the destination and the country. In addition to the species of game to be hunted, the image characteristics, beliefs and experiences associated with the hunting area are also an important factor in the decision of guests, which is why branding, i.e. communicating the value and uniqueness of the experiences offered in a credible and convincing way, and thus clearly distinguishing themselves from their competitors, has become a priority for players in the hunting tourism sector. The organisation is the only one in the world to have been awarded the "Edmond Blanc" award by the International Council for Game and Wildlife Conservation on 2 occasions, with 60,000 hectares of land, which currently produces a world record number of fallow deer trophies. The Gúth Forestry welcomes around 500 guest hunters a year, with an average stay of 3 days. The aim of this case study is to show how the 5-step brand pyramid - based on the integration of objective characteristics and guest perceptions - can be used to identify the distinctive character traits that provide the basis for positioning in a hunting area with international appeal.

A „vadászat” mára markáns turisztikai motiváció lett, és egyértelművé vált a „vadászati turizmus” ország-és desztinációimázs alakulásában játszott szerepe. A vadászati turizmus a „niche” turizmus egyik formájának tekinthető, ami egyfajta autentikus környezetben megvalósuló, speciális érdeklődési kör által motivált turisztikai forma, ennek megfelelően a fogyasztóknak csak egy szűkebb rétegét érinti. A Magyarországra látogató külföldi vendégvadászok száma folyamatosan növekvő tendenciát mutat, 2022-ben számuk 29.000 fő volt. A hazánkba érkező külföldi vadászok a vadásztatók által kidolgozott szolgáltatásfolyamatba bekapcsolódva, a – szolgáltatók asszisztenciájával – élik át élményeiket. Az egyes szolgáltatáselemekkel való kapcsolatuk tapasztalata alapján kialakul elégedettségük vagy elégedetlenségük az adott szolgáltatóval kapcsolatban, de átélt élményük alapjaiban befolyásolja, alakítja az elejtés helyéről, körülményeiről; vagyis az adott desztinációról, illetve az országról kialakuló képet, az imázst is. A vendégek döntésében az elejteni kívánt vadfaj mellett fontos szempont a vadászterülethez kapcsolódó imázsjellemzők, hiedelmek, tapasztalatok is, ezért mára a vadászturisztikai szektor szereplő számára is kiemelt fontosságúvá vált a márkázás, vagyis a kínált élmények értékének és egyediségének hiteles és meggyőző módon való kommunikálása, ezáltal pedig maguk versenytársaiktól való egyértelmű megkülönböztetése. A – jelenleg is világrekordnak számító dámszarvas trófeát produkáló – 60.000 ha-on gazdálkodó szervezet a világon egyedülállóként 2 alkalommal kapta meg a Nemzetközi Vadászati és Vadvédelmi Tanács „Edmond Blanc” díját. A Gúthi erdészet évente kb. 500 vendégvadászt fogad, az átlagos tartózkodási idő 3 nap. Az esettanulmány jellegű tanulmány célja bemutatni, hogy hogyan határozhatóak meg az 5 lépcsős márkapiramis segítségével – az objektív jellemzők és a vendégek percepcióinak integrálása alapján – a pozícionáláshoz alapot szolgáltató markáns karakterjellemzők egy nemzetközi vonzerővel is rendelkező vadászterület esetében.

Резюме. Зараз «полювання» стало помітною туристичною мотивацією, і стала зрозумілою роль «мисливського туризму» в розвитку іміджу країни та дестинацій. Мисливський туризм можна вважати формою «нішевого» туризму, яка є формою туризму, що відбувається в своєрідному автентичному середовищі та мотивується особливим інтересом, що зачіпає лише більш вузький сегмент споживачів. Кількість іноземних гостей-мисливців, які відвідують Угорщину, демонструє постійну тенденцію до зростання, у 2022 році їх кількість становила 29 тис. Іноземні мисливці, які приїжджають до нашої країни, отримують свій досвід, долучаючись до процесу обслуговування, розробленого мисливцями за сприяння постачальників послуг. На основі досвіду їхніх відносин з кожним елементом послуги формується їхнє задоволення чи незадоволення даним постачальником послуг, але на їхній досвід фундаментально впливають і формуються місце та обставини падіння; тобто імідж даного пункту призначення чи країни також. У рішенні гостей, окрім видів дичини, яку вони хочуть убити, також важливим аспектом є імідж, переконання та досвід, пов’язані з територією полювання, тому брендинг, тобто передача цінності та унікальності пропонованого досвіду в автентичній і переконливій формі, тепер набуває першочергового значення для гравців у секторі мисливського туризму, чітко відрізняючи себе від своїх конкурентів. Організація, яка обробляє 60 тис. га, що досі вважається світовим рекордом трофея лані, двічі отримувала нагороду «Едмонд Блан» Міжнародної ради з полювання та охорони дикої природи. Лісове господарство Гут приймає близько 500 гостей-мисливців, середній термін перебування яких – 3 дні. Мета цього тематичного дослідження полягає в тому, щоб продемонструвати, як 5-ступеневу піраміду бренду можна використовувати для визначення характерних рис, що виступатимуть основою для покращення позиціонування мисливського району на основі інтеграції об’єктивних характеристик і сприйняття гостей.
Az 5 lépcsős márkamenedzsment alkalmazásának lehetőségei a Nyírerdő Zrt gúthi vadászterületén
Вступ до 5-крокових умов управління брендом для "Мисливська територія Гут" АТ "Нірердо"
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/6
Keywords: hunting tourism; customer satisfaction; tourism brand; 5-step brand pyramid